Comparing polysaccharide decomposition between the type strains Gramella echinicola KMM 6050T (DSM 19838T) and Gramella portivictoriae UST040801-001T (DSM 23547T), and emended description of Gramella echinicola Nedashkovskaya et al. 2005 emend. Shahina et al. 2014 and Gramella portivictoriae Lau et al. 2005. Issue 1 (December 2016) - Panschin, Irina; Huang, Sixing; Meier-Kolthoff, Jan; Tindall, Brian; Rohde, Manfred; Verbarg, Susanne; Lapidus, Alla; Han, James; Trong, Stephan; Haynes, Matthew; Reddy, T.; Huntemann, Marcel; et al.
Abstract Strains of the genusGramella (familyFlavobacteriacae, phylumBacteroidetes ) were isolated from marine habitats such as tidal flat sediments, coastal surface seawater and sea urchins.Flavobacteriaceae have been shown to be involved in the decomposition of plant and algal polysaccharides. However, the potential to decompose polysaccharides may differ tremendously even between species of the same genus.Gramella echinicola KMM 6050T (DSM 19838T ) andGramella portivictoriae UST040801-001T (DSM 23547T ) have genomes of similar lengths, similar numbers of protein coding genes and RNA genes. Both genomes encode for a greater number of peptidases compared to 'G. forsetii '. In contrast to the genome of 'G. forsetii ', both genomes comprised a smaller set of CAZymes. Seven polysaccharide utilization loci were identified in the genomes of DSM 19838T and DSM 23547T . BothGramella strains hydrolyzed starch, galactomannan, arabinoxylan and hydroxyethyl-cellulose, but not pectin, chitosan and cellulose (Avicel). Galactan and xylan were hydrolyzed by strain DSM 19838T, whereas strain DSM 23547T hydrolyzed pachyman and carboxy-methyl cellulose. Conclusively, bothGramella type strains exhibit characteristic physiological, morphological and genomic differences that might be linked to their habitat. Furthermore, the identified enzymes mediating polysaccharide decomposition, are of biotechnological interest.